Conservatory Students’ Music Performance Anxiety and Educational Expectations: A Qualitative Study - Okan, Hepsen; Usta, Buse (Asian Journal of Education and Training, 2021)
Music performance anxiety (MPA) can seriously and negatively affect musicians’ performance and quality of life—physically, mentally, and behaviorally. In the present study, factors related to the MPA of students receiving classical Western music education in the conservatory in a holistic framework were examined to ascertain the physical, mental, and behavioral symptoms; temporal processes; environmental factors; coping strategies; and educational expectations and desires related to this condition. In addition to investigating causative factors in such a framework, the content analysis method was used on data collected from semi-structured interviews with conservatory students. The results show that the main causative factors of MPA included a jury’s negative evaluation, attitudes, and/or behaviors; their symptoms included trembling, muscle contraction, and distraction. The main coping strategy among participants was positive self-talk; remarkably, they had no theoretical knowledge of positive self-talk. Most significantly, considering that performance is integral to musical education training, students stated that the conservatory needs to integrate into the curriculum a course, counseling, and activities that address MPA.